Compound Heterozygous Variants of CYP27B1 Causing Autosomal Recessive Vitamin D-Dependent Rickets Type 1A in an Indian Child - Mitesh Kakkad; Khyati Kakkad; Chirantap Oza (Wolters Kluwer Medknow Publications, 2024)
Background: Vitamin D-dependent rickets Type 1A (VDDR-1A) is a rare cause of rickets occurring due to variants of CYP27B1 responsible for encoding enzyme 1ά hydroxylase. Clinical Description: We report a 17-months-old girl who presented to us with clinical and radiological features of rickets. The biochemistry investigations suggestive of low calcium, low phosphorous, markedly elevated alkaline phosphatase and parathyroid hormone, high-normal 25 hydroxy Vitamin D level and inappropriately normal 1,25 dihydroxy Vitamin D levels, and no response to oral calcium and Vitamin D supplementation, prompted the diagnosis of VDDR-1A, which was proven genetically with a novel compound heterozygous variant. Management and Outcome: She was treated with oral calcitriol 1.5 μg/day and oral elemental calcium at 500 mg/day; after which at the 3-month follow-up, improvement in clinical, biochemical, and radiological features was observed. Conclusion: Following a clinical diagnosis of VDDR, genetic analysis is preferable to identify the variant and hence understand the genotype-phenotype correlation.